Immunology of renal cell carcinoma - Żołnierek, Jakub; Wysoki, Piotr; Leśniewski-Kmak, Krzysztof; Nurzyński, Paweł (Contemporary Oncology/Współczesna Onkologia, 2007)
Renal cell carcinoma is specific due to its tight relation between tumor origin, development, progression and responseveness of host immune system. Not only clinical data but also molecular studies support this observation. The paper is a short discussion of role that immune system plays in development of renal carcer.